IS CURRENT ENGLISH LANGUAGE CURRICULUM AND ITS PRACTICE DESIGNED TO DEVELOP YOUNG LEARNERS’ COMMUNICATIVE COMPETENCE - Efendi, Tri Achmad; Prihantini , Apsari Fajar; Miranda, Olivia Elsa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the alignment of the Merdeka Curriculum in Indonesia with the goal of fostering young learners’ communicative competence in English. A qualitative approach was utilized, including document analysis, interviews and classroom observations. The study involved three English teachers (one from a private elementary and two from public schools), and three classes were to be observed. Findings reveal that while the curriculum is conceptually designed to develop communicative skills progressively, from oral to written language, its implementation often falls short. Observed teaching practices largely remain teacher-centered, relying on traditional methods such as the Grammar-Translation Method, and provide limited opportunities for meaningful, interactive communication. Textbook analysis indicates that while the resources align with communicative principles, their use in classrooms is often inconsistent with the curriculum's objectives. Assessment practices focus heavily on written skills and vocabulary, neglecting oral communication. The study concludes that the success of the Merdeka Curriculum hinges on equipping teachers with the training and tools necessary to adopt student-centered, communicative approaches, thus bridging the gap between curriculum design and classroom practice. Recommendations include targeted professional development and systemic evaluation mechanisms to ensure alignment with 21st-century educational goals.